Learning C# design patterns : a developer's guide to creational, structural, behavioural and MVC patterns - Welch, Keith; Safari eBooks ([Place of publication not identified] : Infinite Skills, 2015)
"In this Learning C# Design Patterns training course, expert author Keith Welch will teach you about design patterns, and how to use them to create reusable, maintainable code. This course is designed for users that already have experience with C#, as well as basic object-oriented programming principles."--Resource description page.
Title from resource description page (viewed May 11, 2015)
Presenter, Keith Welch.
Keywords: C# (Computer program language); Object-oriented programming languages; Electronic books